Social Action of Conversion in Islamic Art: Study on the Larasmadya Art Form in the Sleman Geocultural Region - Sutiyono Sutiyono (Indonesian Journal of Geography, 2015)
The research concerned here had the purpose of learning the rationality in the social action of conversion by the farmer communities supporting the Larasmadya art form in the Sleman geocultural region. The research was qualitative in approach. The research subjects were members of the farmer communities supporting the Larasmadya art who previously supporting the Slawatan Maulud art form. The research data were compiled by means of observations, interviews, and documentation. These data were analyzed through the phases of data collection, data reduction, data examination, and drawing the conclusion. Data validation was done by means of triangulation. The research results in relation with rationality in the social action of conversion by the communities supporting the Larasmadya art form in the Sleman geocultural region indicate the following. (1) The Larasmadya art form uses the text called Serat Wulang Reh. The text contains Javanese songs influenced by Islam. In addition, the text of the songs in the Larasmadya art form depicts the life of the farmer communities supporting the Larasmadya art form in the Sleman geocultural region. (2) The presence of the Larasmadya art form implies a process of making Islam native in the Sleman geocultural region.